2011
DOI: 10.1007/s10921-011-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bends on the Long-Range Microwave Inspection of Thermally Insulated Pipelines for the Detection of Water

Abstract: The detection of corrosion under insulation is an ongoing challenge in the oil and gas industry. An early warning of areas of pipe at risk of corrosion can be obtained by screening along the length of the pipeline to inspect the insulation layer for the presence of water, as water is a necessary precursor to corrosion. In a recent paper [Jones et al. in J. Nondestruct. Eval. 2011] we have shown that long-range detection of water volumes can be achieved with microwave signals, using the structure of the clad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Demma et al [18] used finite element (FE) analysis to study the transmission and reflection coefficient of guided wave in a bend and indicated that the amplitude of reflected signal increases with the cross sectional area loss of the pipe caused by the defect [19]. A comprehensive study of the effects of bending angles on the transmission coefficient of T mode was reported in [20] by R. E. Jones using simulation and experimental methods. Nishino et al [21] detected defects in circumferential welds before and after pipe bend using the T(0,1) mode ultrasonic guided wave and a wideband laser ultrasonic system was used to describe the propagation phenomena of wideband guided wave in bended pipes with time-frequency analysis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Demma et al [18] used finite element (FE) analysis to study the transmission and reflection coefficient of guided wave in a bend and indicated that the amplitude of reflected signal increases with the cross sectional area loss of the pipe caused by the defect [19]. A comprehensive study of the effects of bending angles on the transmission coefficient of T mode was reported in [20] by R. E. Jones using simulation and experimental methods. Nishino et al [21] detected defects in circumferential welds before and after pipe bend using the T(0,1) mode ultrasonic guided wave and a wideband laser ultrasonic system was used to describe the propagation phenomena of wideband guided wave in bended pipes with time-frequency analysis [22].…”
Section: Introductionmentioning
confidence: 99%
“…This thesis instead focuses on a recent guided microwave method that has been introduced to screen an extended length of pipeline for the presence of wet insulation from a single sensor position [11,12]. Here, the pipe and metallic cladding naturally form a large coaxial transmission line in which the insulation acts as a dielectric and supports the propagation of microwave signals.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments conducted on a 6" diameter pipe with 3" thickness insulation have shown that water volumes equivalent to 5% of the insulation annulus cross-sectional area are readily detectable [11]. Importantly, the microwave signal can travel through bends and supports with limited attenuation [12] thus opening the possibility for monitoring complex pipeworks such as those present in refineries and other petrochemical plants.…”
Section: Introductionmentioning
confidence: 99%
“…Microwaves are part of the electromagnetic spectrum with wave lengths in the centimeter range and frequencies from 0.3 to 300 GHz [1]. Microwave technique is well suited to characterize the properties of nonconductive or weakly conductive materials in noncontact way.…”
Section: Introductionmentioning
confidence: 99%